Is macroprudential policy driving savings? - Teixeira, André (2021)
This paper shows that the recent surge in savings is a result of tighter macroprudential policy. Using a difference-in-differences approach with staggered treatment adoption, we find that households in EU countries that adopted macroprudential policy between 2000 and 2019 increased their savings up to one third more than households in countries without macroprudential policy. Furthermore, our results indicate that the loan-to-value ratio explains most of the variation on savings. Finally, we find that a longer exposure to macroprudential policy exacerbates savings with searing consequences on growth.